2022
DOI: 10.24251/hicss.2022.488
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Wrist-worn Transdermal Alcohol Biosensor to Collect Data in the Field

Abstract: Transdermal alcohol monitoring allows for continuous, non-invasive, objective, and remote measurement of alcohol consumption. We evaluated feasibility and acceptability of participant use of the BACtrack Skyn biosensor bracelet in daily life. Heavy drinkers (n=20) wore the Skyn and self-reported drinking behavior for 7 days, followed by an individual interview. Recruitment and retention benchmarks were met, supporting feasibility. Participants provided both positive and constructive feedback on the Skyn during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Additional information on error rates in more recent new‐generation sensor device builds is critical in determining the feasibility of applications for these sensors. Second, studies to date have featured extremely small sample sizes (Fairbairn & Kang, 2019; Wang et al, 2019) and a select few have sought to validate new‐generation sensors in field settings (Ash et al, 2022; Merrill et al, 2022; Wang et al, 2021). We thus have little sense for how the accuracy of transdermal BAC estimates might be impacted given larger datasets available for model training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional information on error rates in more recent new‐generation sensor device builds is critical in determining the feasibility of applications for these sensors. Second, studies to date have featured extremely small sample sizes (Fairbairn & Kang, 2019; Wang et al, 2019) and a select few have sought to validate new‐generation sensors in field settings (Ash et al, 2022; Merrill et al, 2022; Wang et al, 2021). We thus have little sense for how the accuracy of transdermal BAC estimates might be impacted given larger datasets available for model training.…”
Section: Introductionmentioning
confidence: 99%
“…First, although early hand‐assembled prototypes of new‐generation transdermal sensors showed high failure rates (Ash et al, 2022; Fairbairn & Kang, 2019)—with sensor failure rate ranging from 18% to 38%—relatively little is known of the performance of these sensors beyond the prototype phase. Three studies to date have reported on error rates of (non‐prototype) new‐generation sensors, one of which featured expert users rather than community samples (Wang et al, 2021), and two others that recruited a relatively small number of community participants (Ash et al, 2022; Merrill et al, 2022). Additional information on error rates in more recent new‐generation sensor device builds is critical in determining the feasibility of applications for these sensors.…”
Section: Introductionmentioning
confidence: 99%
“…A new‐generation wrist‐worn transdermal alcohol biosensor, the BACtrack Skyn (BACtrack, Inc.), resembles a fitness tracker and offers a promising alternative to the SCRAM‐CAM. To date, small studies using the Skyn demonstrate high user acceptability (Merrill et al, 2022) and lab‐based studies in which alcohol administration is used in a controlled setting show strong correlations between TAC and breath alcohol concentration (BrAC; Fairbairn & Bosch, 2021; Fairbairn & Kang, 2019; Merrill et al, 2022; Wang et al, 2021). Thus, although there is evidence of valid measurement of alcohol use in controlled settings with the Skyn, and acceptability of the Skyn in field studies, additional validation is needed in order for the Skyn to be incorporated into future large‐scale studies and interventions.…”
Section: Introductionmentioning
confidence: 99%